HUBUNGAN TINGKAT PENGETAHUAN, SIKAP IBU DAN DUKUNGAN SUAMI DENGAN PEMILIHAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) DI PONKESDES PRONOJIWO PUSKESMAS PRONOJIWO KABUPATEN LUMAJANG - Ika Rini Puspitasari; Nova Hikmawati; Sri Wahyuningsih (NHM PRESS, 2023)
The high rate of population growth is a problem faced by Indonesia.Long-Term Contraceptive Method is an efficient and suitable contraceptive for a long time to reduce pregnancy. The design of this study is a statistical analysis of correlation with a cross- sectional approach.The population in this study averaged 30 visits by active family planning participants at Ponkesdes Pronojiwo from April 10 to April 30, 2023. The number of samples used as many as 30 people were selected using accidental sampling techniques,and data collection using valid and reliable questionnaires. The results of data analysis based on the Chi - Square Test showed that there was a correlation between the level of knowledge (p = 0.048), maternal attitude (p = 0.002), and husband support (p = 0.001) with the election of LARCs.The conclusion is that the level of good knowledge describes a broader insight so that it is easy to receive information and make appropriate decisions, and respondents are willing to use and choose LARCs, which certainly cannot be separated from the support of husbands who play a role in decision making. Advice for health workers is more optimal to provide IEC and Informed Choice to prospective KB acceptors, especially LARCs .So that in the future it can increase the number of long-term KB acceptors.